Not Merely a Question of Work: Social Capital for Professional Carers, Between Reciprocity, Trust and Emotional Involvement - Gucciardo, Gaetano; Affatigato, Rita; Di Rosa, Roberta Teresa (Italian Sociological Review, 2025)
The relationship between social capital and care work provides an invaluable area for research. Recently, researchers have focused on the relationship between social capital and the care work provided to those with long-term needs by individuals and family members. One such study focused on the social capital available to family carers (Ng et al., 2022). In this paper, we attempt to explore a different dimension. Firstly, we focus our attention on paid care work. At the centre of this is the figure of the professional caregiver. From here, we look at their relationship with the person for whom they are caring and also with a reference figure that the caregiver has identified as their support. We will closely examine these two relationships to see whether, and under what conditions, forms of social capital, in terms of trust, reciprocity and support within the caregiver network, are triggered and generated.